Association of Antidepressant Continuation in Pregnancy and Infant Birth Weight. Issue 4 (July 2021) - Wartko, Paige D.; Weiss, Noel S.; Enquobahrie, Daniel A.; Chan, K. C. Gary; Stephenson-Famy, Alyssa; Mueller, Beth A.; Dublin, Sascha
Abstract: Purpose: The aim of the study was to evaluate the association of antidepressant continuation in pregnancy with infant birth weight among women using antidepressants before pregnancy. Methods: This retrospective cohort study used electronic health data linked with state birth records. We identified singleton live births (2001–2014) to enrolled women with 1 or more antidepressant prescriptions filled 6 months or less before pregnancy, including "continuers" (≥1 antidepressant fills during pregnancy, n = 1775) and "discontinuers" (no fill during pregnancy, n = 1249). We compared birth weight, small or large for gestational age (SGA or LGA), low birth weight (LBW; <2500 g), and macrosomia (>4500 g) between the 2 groups, using inverse probability of treatment weighting to account for pre-pregnancy characteristics, including mental health conditions. Results: After weighting, infants born to antidepressant continuers weighed 71.9 g less than discontinuers' infants (95% confidence interval [CI], −115.5 to −28.3 g), with a larger difference for female infants (−106.4 g; 95% CI, −164.6 to −48.1) than male infants (−48.5 g; 95% CI, −107.2 to 10.3). For female infants, SGA risk was greater in continuers than discontinuers (relative risk [RR], 1.54; 95% CI, 1.02 to 2.32). Low birth weight risk was greater in continuers with 50% or more of days covered (RR, 1.69; 95% CI, 1.11 to 2.58) and exposure in the second trimester (RR, 1.53; 95% CI, 1.02 to 2.29), as compared with discontinuers. Conclusions: Depending on infant sex, as well as duration and timing of use, continuation of antidepressant use during pregnancy may be associated with lower infant birth weight, with corresponding increases in LBW and SGA. Abstract : Supplemental digital content is available in the text.